The brief COPE: a factorial structure for incarcerated adults - Power, Jenelle (Criminal justice studies, 2021)
Research suggests that coping deficits play an important role in understanding offender behavior. The present study examines the use of the Brief COPE among a sample of 377 federally incarcerated Canada inmates. Using principal axis factor analysis, followed by confirmatory factor analysis, an eight factor structure was supported: (1) Support Seeking (α =.86); (2) Acceptance (α =.76); (3) Disengagement (α =.75); (4) Active Coping (α =.64); (5) Substance Use (α =.90); (6) Humor (α =.78); (7) Religion (α =.84); and (8) Self-Blame (α =.77). Factors were comprised of two to four items, with five that did not load onto any factor. Findings indicate that the Brief COPE constitutes a short, accessible, and validated measure of coping styles that is suitable for use with offender populations.